PENGARUH APLIKASI PEMBENAH TANAH HAYATI DAN DOSIS PUPUK ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) - nurul fakhriyah; Abdul Basit; Maria Ulfah (AGRONISMA, 2021)
To increase crop production and maintain soil health and soil quality, the addition of biological soil amandement can be used so as to reduce the use of inorganic fertilizer because soil amandement have good microba content for the soil. This study aims to determine the effect of giving soil amandement and reducing the dose of inorganic fertilizers on the growth and yield off eggplant (Solanum melongena L.). This research took place in Karangjadi Hamlet, Ardimulyo Village, Singosari District, Malang Regency on 07 October 2020 – 28 February 2021with an altitude of ± 487 mdpl, the average air temperature ranging from 17 – 27 oC. The research design used was a factorial design which was compiled with the basic design of a 2 factor Randomized Block Design (RAK). he first factor consists of T0 (Without soil amandement) and T1 (With soil amandement). The second factor consists of 5 levels, namely P0 (No dose of NPK fertilizer), P1 (25% dose of NPK fertilizer), P2 (50% dose of NPK fertilizer), P3 (75% dose of NPK fertilizer) and P4 (100% dose of NPK fertilizer). There were 10 treatments which were repeated 3 times, and each plot contained 4 plants so that the number of samples observed was 120 plants. Statistical analysis test with ANOVA and 5% BNJ follow-up test. The results of the analysis (ANOVA) showed that in general the combination of T1P1 (giving soil amandement + 25% dose of NPK fertilizer) yields tended to be higher for the parameters of the total number of fruit per plant, fruit weight per plot, and fruit weight per hectare of 23.00, 515.37 grams.and fr 16.85 tons.